2003
DOI: 10.1093/bmb/66.1.213
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic and familial CJD: classification and characterisation

Abstract: Prion diseases are unique transmissible neurodegenerative diseases that have diverse phenotypes and can be familial, sporadic, or acquired by infection. Recent findings indicate that the PrP genotype and the PrP(Sc) type have a major influence on the disease phenotype in both sporadic and familial human prion diseases. This review attempts to classify and characterise sporadic and familial Creutzfeldt-Jakob disease (CJD) as a function of these two disease determinants. Based on the genotype at codon 129 on bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
582
0
31

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 488 publications
(641 citation statements)
references
References 96 publications
28
582
0
31
Order By: Relevance
“…Linkages between familial prion diseases and mutations in the gene encoding human prion protein were reported and over 20 such mutations have been shown to date to segregate familial CJD, GSS and FFI [1,19,20]. The D178N mutation is one of the most intriguing disease-related mutations and leads to different phenotypes of human prion disease depending upon the polymorphism at position 129.…”
Section: Influence Of the Pathogenic Mutations On The Conformational mentioning
confidence: 99%
“…Linkages between familial prion diseases and mutations in the gene encoding human prion protein were reported and over 20 such mutations have been shown to date to segregate familial CJD, GSS and FFI [1,19,20]. The D178N mutation is one of the most intriguing disease-related mutations and leads to different phenotypes of human prion disease depending upon the polymorphism at position 129.…”
Section: Influence Of the Pathogenic Mutations On The Conformational mentioning
confidence: 99%
“…Although sCJD is rare, with an incidence of 0.6-1.2 per million, it accounts for about 85% of all recognized human cases of prion disease (Brandel et al, 2000;Hill et al, 2003). Two predominant PrP sc types have been identified, based on the gel mobility of the PrP sc fragments resistant to proteinase K (PK) treatment, and they are associated with different CJD phenotypes (Cali et al, 2006;Gambetti et al, 2003;Monari et al, 1994;Petersen et al, 1994). Parallel to this, PRNP polymorphism at codon 129 (Met 129 →Val) modulates sensitivity to CJD, and methionine homozygosis is a risk factor for sporadic and variant CJD (Collinge, 1999;Ladogana et al, 2005;Palmer et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Western blot of brain tissues obtained at biopsy and autopsy demonstrated the presence of rPrP Sc type 1 (Figure 2), whereas neuropathological examination revealed severe spongiform degeneration, astrogliosis, and the presence of ballooned neurons associated with weak PrP immunostaining, displaying a fine granular pattern (Figures 1 and 2). 33 Cumulatively, these characteristics unquestionably define this case as sCJDVV1. 33 Our study indicated that most of the PrP in the uterus, placenta, and amniotic fluid is truncated at the N-terminal and shares gel mobility (ϳ18 kDa) with C1, a C-terminal PrP fragment generated during normal metabolism of PrP C in the brain.…”
Section: Discussionmentioning
confidence: 98%
“…33 Cumulatively, these characteristics unquestionably define this case as sCJDVV1. 33 Our study indicated that most of the PrP in the uterus, placenta, and amniotic fluid is truncated at the N-terminal and shares gel mobility (ϳ18 kDa) with C1, a C-terminal PrP fragment generated during normal metabolism of PrP C in the brain. 12 It is noteworthy that the gel mobility of the PrP fragment present in these tissues is similar to that of the urine PrP, but different from that of CSF and brain, in agreement with earlier observations.…”
Section: Discussionmentioning
confidence: 98%